Effects of microwave on drug release profiles of guluronic acid-rich alginate spheroids / Nurul Hidayah Mohd Salleh - Mohd Salleh, Nurul Hidayah (2015)
Since the last decade, various formulation and processing approaches have been introduced in drug delivery system design to negate the propensity of drug release from dosage form in the acidic gastric region. Polysaccharides have been employed in the formulation of pharmaceutical drug delivery system for small molecule drug. Nevertheless, the formed matrix frequently is found to have a porous structure. Consequently, an uncontrollably fast release rate of small molecule drug is resulted. Such rate of drug release is undesirable in the case of the need to target the drugs to the lower part of gastrointestinal tract, particularly, the colon. Alginate is a type of polysaccharide that has been employed in the formulation of pharmaceutical drug delivery system for small molecule drug. It is produced from brown seaweeds, and is biocompatible, non-toxic, non-immunogenic and biodegradable. The present study investigates small molecule drug release from spheroids prepared from guluronic acidrich alginate. The drug release property of these spheroids was examined with reference to additive and microwave effects as formulation and processing variables respectively. The spheroids were prepared by extrusion-spheronization technique using microcrystalline cellulose as spheronization aid, zinc chloride as crosslinking agent, chlorpheniramine maleate as model water-soluble drug, stearic acid and 1 2 - hydroxystearic acid as additives. The formed spheroids were subjected to size, shape, drug content, drug release, zinc release, fourier transform infrared spectroscopy, differential scanning calorimetry and surface morphology analysis. They were treated by microwave at 80 W for 5 to 40 min when required. Alginate spheroids demonstrated a fast drug release characteristics and such fast release attribute can be reduced through zinc alginate crosslinkage formation. The zinc alginate spheroids exhibited a lower level of drug release despite the matrix was disintegrated into fines particles which had a larger specific surface area for drug dissolution. Loading of stearic acid or 1 2 -hydroxystearic acid into alginate or zinc alginate spheroids did not substantially retard drug release though these fatty acids were relatively hydrophobic. Overall, the treatment of alginate-based spheroids by microwave tended to bring minor changes in drug release property except that of zinc alginate-1 2 -hydroxystearic acid spheroids where O-H moiety of fatty acid and alginate responded to the influence of microwave.